Reflections and implementation strategies for constructing a standard system for deep coalbed methane exploration and exploitation - Xinjun CHEN; Zengqin LIU; Baojian SHEN; Shihu ZHAO; Jiaqi ZHANG; Jincheng YE (Meitian dizhi yu kantan)
ObjectiveDeep coalbed methane (CBM; burial depths: > 1500 m) in China holds considerable resource potential. As a strategic clean energy, deep CBM is exhibiting increasingly high value of exploitation and utilization. This is of great practical significance for China’s energy structure transformation and the achievement of peak carbon dioxide emissions and carbon neutrality in the country. In recent years, breakthroughs have been made in deep CBM exploration in basins such as Ordos, Sichuan, and Junggar, with a single-well daily gas production exceeding 100 000 m3, marking the initial achievement of large-scale deep CBM exploitation. However, the existing standard system, primarily designed for shallow CBM resources (burial depths: < 1 000 m), is difficult to adapt to the complex, unique geological conditions of deep CBM such as high temperature, high pressure, high stress, strong heterogeneity, and high free gas content. This leads to insufficient technical adaptability and pronounced risks of safety and environmental protection in the exploration and exploitation of deep CBM. MethodsThrough a systematic analysis of differences in geological and engineering characteristics between shallow and deep CBM, this study proposed a standard system framework following three dimensions (i.e., geological complexity, technical adaptability, and industrial and ecological collaboration) and four principles (scientific, systematic, practical, and dynamic natures). Furthermore, this study determined the staged objectives for the standard system construction. Specifically, the short-term objective is to establish a geological and engineering integrated standard framework by focusing on the improvement in exploration accuracy and the optimization of exploitation processes, aiming to drive technological innovations and industrial transformation and upgrading. The medium-term objective is to establish a technical standard cluster covering the entire industry chain while promoting the whole life cycle risk management, with the purpose of achieving efficient resource utilization and maximizing investment returns. The long-term objective is to participate in the formulation of international standards and intensify international technological exchanges and cooperation, thereby enhancing the international competitiveness of China’s deep CBM industry. Results and ConclusionsThe results of this study indicate that the standard system for the deep CBM industry should incorporate six major fields: the basic and general aspect, geological exploration, seismic surveys and logging, exploitation assessment, engineering construction, and safety and environmental protection. It is recommended to highlight the construction of core technical standards of reservoir assessment, sweet spot assessment, and fracturing stimulation following a standard development strategy of inheritance-based improvement combined with revolutionary innovations. It is suggested that a standardized working framework should be established more quickly via strategic pathways including the construction of a standard system framework, the formulation and revision of key standards, the combination of technological innovations and standardization, international cooperation and exchanges, and political support and guarantee. The purpose is to provide a guarantee in terms of systems and technical support for the high-quality development of the deep CBM industry.